Studi Pengaruh Fraksi Volume dan Susunan Serat Terhadap Kekuatan Tarik dan Bending Komposit Resin Berpenguat Serat Rotan (Calamus Trachycoleus) - Hendri Hestiawan (JURNAL MECHANICAL, 2014)
Use of natural fiber composite material started being developed in the manufacturing industry. Progress is due to the composite nature of the privilege of the composite itself, such as: has a low density, capable of biodegradable, recyclable, has good mechanical properties, and can be renewed because it comes from nature. This research aims to determine the effect of fiber volume fraction and the composition to the tensile strength and bending strength on rattan fiber reinforced composites.The research material is rattan fiber, epoxy resin and catalyst methyl ethyl ketone peroxide (MEPOXE). Shape of the specimen based on the ASTM D3039 standard for tensile test and ASTM D790-03 for the bending test. Research specimens varied in aggregate form filler fibers are straight, cross, and random with fiber volume fraction of 10%, 20%, 30%, and 40%. Manufacture of specimens using hand lay-up method. To determine the mechanical properties of the material bending test and tensile test and photo macro structure.The results showed that the addition of fiber volume fraction resulted in an increase in tensile stress and bending. The highest tensile stress occurs on the fiber volume fraction of 40% with a straight fiber composition of 31.21 MPa. The highest bending voltage obtained at 40% fiber volume fraction and the fiber composition of the cross of 194.12 MPa. Observations of macro structure indicate that fracture surface is relatively flat and shiny indicating that the rattan fiber reinforced composites are brittle. Keywords: Composites, the rattan fiber, volume fraction, fiber composition, epoxy resin